Analisis Kemampuan Pemecahan Masalah Siswa Pada Materi Statistika Kelas XI Mas Al Washliyah 49 Pasar Lembu - Dila Safriani; Syahriani Sirait (JURNAL MATHEMATIC PAEDAGOGIC, 2026)
This study aimed at describing students’s mathematical problem solving ability. This research is a qualitative descriptive study. The subject of this research  is statistics. The subjects in this study were students of MAS Al Washliyah 49 Pasar Lembu at class XI IPA totaling 25 students. Data collection instruments used included test questions totaling questions that referred to indicators of students’ problem solving ability including understanding problems, planning solutions, implementing plans, and reinterpreting them. Data analysis techinques used in this study were to assess the results of student answers and determine the percentage of students’ problem solving ability seen from the low, medium, and high categories. Based on the result of data processing, obtained as many as 6 students (24%) included in the category of “low” or have not been able to carry out the four stages well, and 11 students (44%) included in the category of “medium” or able to carry out category of “high” or have not been able to carry out the fourth stage.